Pengaruh Model Pembelajaran Kooperatif Tipe Scramble Terhadap Hasil Belajar Bahasa Inggris Kelas IV SD - Cindy Dian Lestari; Ujang Efendi; Alif Luthvi Azizah; Fadhilah Khairani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study was the low English learning outcomes of fourth-grade elementary school students. This study aimed to determine the effect of the implementation of the cooperative learning model of the scramble type on the English learning outcomes of fourth-grade students. This research was a quantitative study using a quasi-experimental method with a nonequivalent control group design. The population in this study consisted of 622 students, representing the total number of all fourth-grade students at SD Negeri 2 Jatimulyo. The sample consisted of 52 students, divided into two classes: 26 students in the experimental class and 26 students in the control class. The sampling technique used was purposive sampling. Data collection techniques included tests in the form of multiple choice pretests and posttests, and non-test techniques in the form of observation sheets. The data analysis technique used was simple linear regression. The results of this study showed a significant effect of the implementation of the scramble type cooperative learning model on the English learning outcomes of fourth-grade students.